The role of the different CD3γ domains in TCR expression and signaling - Beatriz Garcillán; Rebeca F. Megino; Marta Herrero-Alonso; Alberto C. Guardo; Veronica Perez-Flores; Claudia Juraske; Claudia Juraske; Claudia Juraske; Claudia Juraske; Vincent Idstein; Vincent Idstein; Vincent Idstein; et al. (Frontiers in Immunology, 2022)
The CD3 subunits of the T-cell antigen receptor (TCR) play a central role in regulation of surface TCR expression levels. Humans who lack CD3γ (γ—) show reduced surface TCR expression levels and abolished phorbol ester (PMA)-induced TCR down-regulation. The response to PMA is mediated by a double leucine motif in the intracellular (IC) domain of CD3γ. However, the molecular cause of the reduced TCR surface expression in γ— lymphocytes is still not known. We used retroviral vectors carrying wild type CD3γ or CD3δ or the following chimeras (EC-extracellular, TM-transmembrane and IC): δECγTMγIC (δγγ for short), γγδ, γδδ and γγ-. Expression of γγγ, γγδ, γδδ or γγ- in the γ— T cell line JGN, which lacks surface TCR, demonstrated that cell surface TCR levels in JGN were dependent on the EC domain of CD3γ and could not be replaced by the one of CD3δ. In JGN and primary γ— patient T cells, the tested chimeras confirmed that the response to PMA maps to the IC domain of CD3γ. Since protein homology explains these results better than domain structure, we conclude that CD3γ contributes conformational cues that improve surface TCR expression, likely at the assembly or membrane transport steps. In JGN cells all chimeric TCRs were signalling competent. However, an IC domain at CD3γ was required for TCR-induced IL-2 and TNF-α production and CD69 expression, indicating that a TCR without a CD3γ IC domain has altered signalling capabilities.